Behavior of bioactive compounds and antioxidant activity of mango (Azucar cultivar) juice during storage at 4 ºC (2019)
ABSTRACT: Mango (Mangifera indica L.) is one the fruits that have shown antioxidant activity and high nutritional value. It was evaluated the effect of storage time and temperature on polyphenol content, ascorbic acid and antioxidant activity of mango (cv. Azucar) juice stored up to 64 days at 4 °C. Total polyphenol content was measured by Folin-Ciocalteu method, mangiferin and ascorbic acid were measured by HPLC (High-Performance Liquid Chromatography) and antioxidant activity was measured by ORAC (Oxygen Radical Absorbance Capacity), and ABTS•+ (2,2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) method. Total phenolic content decreased after 16 days of juice storage. Ascorbic acid values did not show significant differences until 48 days of storage, and mangiferin content was very similar throughout storage time. The antioxidant activity measured by ORAC method was similar until the end of the storage; however, ABTS value decreased after 32 days of juice storage. In conclusion, storage up to 32 days of mango juice at 4 °C did not alter its antioxidant activity and ascorbic acid content.